PENGARUH LATIHAN SWISS BALL TERHADAP RESIKO JATUH PASIEN DIABETES MELLITUS TIPE 2 - Noor Fitriyani Noor Fitriyani; Annisa Cindy Nurul Afni; Maula Maratus Sholihah (UPT PPM Sekolah Tinggi Ilmu Kesehatan Al Irsyad Al Islamiyyah Cilacap, 2022)
Background: Diabetes Mellitus (DM) is a non-communicable disease due to metabolic disorders that must be managed immediately. Type 2 diabetes mellitus has the highest percentage of sufferers.The diagnosis duration of diabetes patients has a high risk of sensitivity and motor symptoms since it has an impact on the risk of falling for the sufferer. An Effort that could be implemented is physical exercise in the form of swiss ball training as one of the diabetic management pillars. Objective: The study was conducted to ascertain the effect of swiss ball exercises on the risk of falling in Type 2 DM patients. Method: This study used a quasi-experiment with a pre-test and post-test one group only design. The total sampling technique of 25 patients with type 2 diabetes mellitus was the participants of the study. The correlation test was analyzed by the Wilcoxon signed-rank test. Result: The study obtained a falling risk score from 25 respondents in the pre- and post- swiss ball exercise intervention with a mean value of 37.64 to 43.48; the standard deviation value from 2.158 to 3.490; minimum value 34 to 37; and the maximum value of 42 to 50. The result of comparative test presented p-value = 0,000 (p-value <0.05). It implied that there is an effect of swiss ball exercises on the risk of falling in type 2 DM patients.Swiss ball exercises could be involved in the physical exercise program for type 2 DM patients with over 45 years old who are at high risk of falling and it was statistically significant.